2022
DOI: 10.1101/2022.10.14.512290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-gene resolution of diversity-driven community overyielding

Abstract: In plant communities, diversity often increases community productivity and functioning, but the specific underlying drivers are difficult to identify. Most ecological theories attribute the positive diversity effects to complementary niches occupied by different species or genotypes. However, the type of niche complementarity often remains unclear, including how complementarity is expressed in terms of trait differences between plants. Here, we use a gene-centred approach to identify differences associated wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In the last years, breeding for more diverse crop systems (i.e. mixtures) has gained more attention (Bourke et al, 2021; Haug et al, 2021; Moore et al, 2022) and genes were identified which might be relevant for breeding in more diverse crop systems (Wuest et al, 2022; Wuest and Niklaus, 2018). Furthermore, a recent study found evidence for genetic and epigenetic evolution of monoculture and mixture ecotypes in grassland species (van Moorsel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, breeding for more diverse crop systems (i.e. mixtures) has gained more attention (Bourke et al, 2021; Haug et al, 2021; Moore et al, 2022) and genes were identified which might be relevant for breeding in more diverse crop systems (Wuest et al, 2022; Wuest and Niklaus, 2018). Furthermore, a recent study found evidence for genetic and epigenetic evolution of monoculture and mixture ecotypes in grassland species (van Moorsel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%